Pengaruh Gaya Kepemimpinan, Beban Kerja dan Disiplin Kerja terhadap Kinerja Karyawan Sub Cabang Corintek Inti Sejahtera Pondok Pekayon Bekasi - Hanna Caroline Patricia; Cahyadi Husadha; Tutiek Yoganingsih (Jurnal Riset dan Inovasi Manajemen, 2024)
This research aims to determine the influence of leadership style, workload and work discipline on employee performance at the Corintek Inti Sejahtera Pondok Pekayon Bekasi sub-branch. The research method used in this research is quantitative research. The sampling technique used a saturated sampling technique through a questionnaire created via Google Form with the criteria for all employees of the Corintek Inti Sejahtera Pondok Pekayon Bekasi sub-branch, totaling 56 employees. The data analysis method uses statistical methods with SmartPLS 4.0 software. The results of this research show that: (1) Leadership style has a positive and significant effect on the performance of employees of the Corintek Inti Sejahtera Pondok Pekayon Bekasi sub-branch, (2) Work load has no partial effect on employee performance of the Corintek Inti Sejahtera Pondok Pekayon Bekasi sub-branch, (3) ) Work discipline has a positive and significant effect on employee performance at the Corintek Inti Sejahtera Pondok Pekayon Bekasi sub-branch, and (4) Leadership style and work discipline have a simultaneous effect on employee performance, but workload does not partially affect employee performance at the Corintek Inti Sejahtera sub-branch. Pondok Pekayon Bekasi.